Forb ecology research in dry African savannas: Knowledge, gaps, and future perspectives. Issue 13 (2nd June 2019) - Siebert, Frances; Dreber, Niels
Abstract: Savannas are commonly described as a vegetation type with a grass layer interspersed with a discontinuous tree or shrub layer. On the contrary, forbs, a plant life form that can include any nongraminoid herbaceous vascular plant, are poorly represented in definitions of savannas worldwide. While forbs have been acknowledged as a diverse component of the herbaceous layer in savanna ecosystems and valued for the ecosystem services and functions they provide, they have not been the primary focus in most savanna vegetation studies. We performed a systematic review of scientific literature to establish the extent to which forbs are implicitly or explicitly considered as a discrete vegetation component in savanna research. The overall aims were to summarize knowledge on forb ecology, identify knowledge gaps, and derive new perspectives for savanna research and management with a special focus on arid and semiarid ecosystems in Africa. We synthesize and discuss our findings in the context of different overarching research themes: (a) functional organization and spatial patterning, (b) land degradation and range management, (c) conservation and reserve management, (d) resource use and forage patterning, and (e) germination and recruitment. Our results revealed biases in published research with respect to study origin (country coverage in Africa), climate (more semiarid than arid systems), spatial scale (more local than landscape scale), the level at which responses or resource potential was analyzed (primarily plant functional groups rather than species), and the focus on interactions between life forms (rather seldom between forbs and grasses and/or trees). We conclude that the understanding of African savanna community responses to drivers of global environmental change requires knowledge beyond interactions between trees and grasses only and beyond the plant functional group level. Despite multifaceted evidence of our current understanding of forbs in dry savannas, there appear to be knowledge gaps, specifically in linking drivers of environmental change to forb community responses. We therefore propose that more attention be given to forbs as an additional ecologically important plant life form in the conventional tree–grass paradigm of savannas. Abstract : Through this systematic review on forb ecology, we evaluate and summarize current knowledge of forbs in dry African savanna ecosystems and conclude that the ecological understanding of savanna community responses to drivers of global environmental change requires knowledge beyond the plant functional group level. Here, we highlight important findings and summarize knowledge gaps and future perspectives for including forbs as an additional ecologically important plant life form in the conventional tree–grass paradigm of savannas.